A low-impurity, high-specific-surface-area ferric phosphate and its preparation method and application
By introducing oxidative gas during the crystal transformation of iron phosphate, the problem of high impurities content of magnesium and manganese in iron phosphate in the traditional one-step process is solved, and iron phosphate with low impurities and high specific surface area is prepared, which improves the performance of lithium iron phosphate positive electrode material.
Patent Information
- Application Number
- CN202410354260.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-03-26
AI Technical Summary
The high content of magnesium and manganese impurities in iron phosphate prepared by the traditional one-step process leads to poor specific capacity and circulation performance of lithium iron phosphate positive electrode material.
During the crystal transformation of iron phosphate, oxidizing gas is introduced. The oxidation of the oxidizing gas always presents trace amounts of trivalent iron ions in the system, inhibiting the formation of impurity phosphate, and obtaining a large specific surface area of iron phosphate in the porous structure through pore formation.
The preparation of iron phosphate with low impurities and high specific surface area has been achieved, and the performance of lithium iron phosphate positive electrode material has been improved, which is suitable for industrial large-scale production.
Smart Images

Figure CN118062816B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium battery materials, and in particular to a low-impurity, high-specific-surface-area iron phosphate and a preparation method and application thereof. Background Art
[0002] Lithium iron phosphate has become the first choice for new energy power batteries due to its high safety and good cycle performance. As the main raw material for preparing lithium iron phosphate, the demand for iron phosphate is also growing continuously.
[0003] At present, in order to reduce production costs, the industry generally uses ferrous sulfate, a byproduct of titanium dioxide, as the iron source for the synthesis of ferric phosphate. However, the impurity content of ferrous sulfate, a byproduct of titanium dioxide, is relatively high. The existing refining and impurity removal methods can only remove the titanium element in ferrous sulfate. A large amount of magnesium and manganese impurities need to be precipitated under alkaline conditions, which makes it impossible to remove them during the refining process. At the same time, the synthesis of ferric phosphate using ferrous sulfate, a byproduct of titanium dioxide, as a phosphorus source using a one-step process still has the problem of high sulfur content. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a low-impurity and high specific surface area iron phosphate and its preparation method and application, aiming to solve the problem of high magnesium and manganese content in iron phosphate prepared by the traditional one-step process.
[0005] In a first aspect, the present invention provides a method for preparing low-impurity and high specific surface area iron phosphate, which comprises:
[0006] Providing a ferrous salt solution and a mixed solution containing an oxidant and a phosphorus source;
[0007] mixing the ferrous salt solution with the mixed solution, and performing a precipitation reaction to obtain a reaction slurry;
[0008] An oxidizing gas is introduced into the reaction slurry, and then the temperature is raised and aged to obtain a hydrated iron phosphate slurry;
[0009] After solid-liquid separation, washing, drying and sintering of the hydrated iron phosphate slurry, low-impurity and high specific surface area iron phosphate is obtained.
[0010] In the embodiments of the present application, an oxidizing gas is introduced during the crystal transformation of iron phosphate. Under the oxidizing action of the oxidizing gas, a trace amount of trivalent iron ions are always present in the system. The trivalent iron ions can suppress the formation of impurity phosphates, thereby obtaining iron phosphate with a low impurity content. At the same time, the introduced oxidizing gas also has a pore-forming effect, and can obtain iron phosphate with a porous structure and a large specific surface area. Therefore, the embodiments of the present application can prepare iron phosphate with low impurities and high specific surface area by a one-step method, which is conducive to the preparation of high-performance lithium iron phosphate positive electrode materials using the low-impurity, high specific surface area iron phosphate.
[0011] In some embodiments, the molar ratio of the oxidant in the mixed solution to the ferrous salt in the ferrous salt solution is (0.35:1)-(0.50:1);
[0012] Preferably, the oxidant comprises at least one of hydrogen peroxide and ammonium persulfate;
[0013] Preferably, the molar concentration of phosphate in the mixed solution is 1.0-3.0 mol / L, and the molar concentration of ferrous ions in the ferrous sulfate solution is 0.5-1.5 mol / L.
[0014] In this embodiment, controlling the phosphate concentration in the mixed solution and the ferrous ion concentration in the ferrous sulfate solution is beneficial to the reaction to generate amorphous ferric phosphate with uniform particle size and low impurity content. Setting the molar ratio of the oxidant in the mixed solution to the ferrous salt in the ferrous salt solution to an appropriate ratio can allow the oxidant to oxidize part but not all of the ferrous ions, that is, a small amount of unreacted ferrous ions are always present in the obtained reaction slurry, which is beneficial to the later stage of the crystal transformation of the amorphous ferric phosphate under the oxidizing action of the oxidizing gas, oxidizing the unreacted ferrous ions into trivalent ferrous ions, thereby inhibiting the formation of impurity phosphates and obtaining a high-purity ferric phosphate product.
[0015] In some embodiments, the aging temperature is set at 80-95° C., and after the reaction slurry changes color, the temperature is kept warm for 30-90 minutes.
[0016] In this embodiment, the aging temperature is set to 80-95°C. After the reaction slurry changes color, it continues to stand and keep warm for a period of time. During the aging stage, the amorphous iron phosphate generated by the reaction is converted into crystalline iron phosphate. The appropriate temperature and insulation time can promote the crystal transformation and obtain a more complete crystal.
[0017] In some embodiments, the molar ratio of phosphorus in the mixed solution to iron in the ferrous salt solution is (1.0:1)-(1.3:1);
[0018] Preferably, the phosphorus source includes ammonium phosphate and phosphoric acid, and the ferrous salt includes ferrous sulfate;
[0019] Preferably, the molar ratio of ferrous salt: ammonium phosphate: phosphoric acid is 1: (0.80-1.05): (0-0.25).
[0020] In this embodiment, by controlling the material ratio of each material in the system, it is beneficial to the reaction to generate amorphous iron phosphate with uniform particle size and low impurity content, as well as the subsequent crystal transformation of amorphous iron phosphate, to obtain an iron phosphate product with high purity, good dispersibility, low impurities and good P / Fe molar ratio stability.
[0021] In some embodiments, the oxidizing gas comprises a gas containing oxygen;
[0022] Preferably, the oxidizing gas includes at least one of air, oxygen, ozone, and compressed air;
[0023] Preferably, the oxidizing gas is selected from compressed air.
[0024] In this embodiment, the oxidizing gas includes a gas containing oxygen. The oxidizing gas is introduced during the crystal transformation of ferric phosphate. Under the oxidizing action of the oxidizing gas, a trace amount of trivalent iron ions are always present in the system. The trivalent iron ions can inhibit the formation of impurity phosphates.
[0025] In some embodiments, solid-liquid separation, washing, drying and sintering of the hydrated ferric phosphate slurry comprises: filtering the hydrated ferric phosphate slurry, washing in countercurrent, drying at 90-110°C, and sintering at 550-650°C.
[0026] In this embodiment, the hydrated ferric phosphate slurry is separated from the solid and liquid and washed to further remove impurities adsorbed on the surface of the ferric phosphate crystals. After drying and sintering dehydration, anhydrous ferric phosphate with a porous structure, a large specific surface area and a low sulfur content (porous structure ferric phosphate impurity sulfur is more likely to escape during the sintering process) can be obtained.
[0027] In the second aspect, the embodiment of the present application also provides a low-impurity and high specific surface area iron phosphate prepared according to the above preparation method, wherein the sulfur content of the low-impurity and high specific surface area iron phosphate is less than 100ppm, Mg is less than 60ppm, Mn is less than 60ppm, the total content of Mg+Mn is less than 100ppm, and the specific surface area is greater than 10m 2 / g.
[0028] In this embodiment, the low-impurity and high specific surface area ferric phosphate prepared has the advantages of low impurity content (especially low magnesium and manganese impurity content), low sulfur content, large specific surface area and porous structure.
[0029] In a third aspect, an embodiment of the present application further provides a lithium iron phosphate positive electrode material, the raw materials of which include the above-mentioned low-impurity and high specific surface area iron phosphate.
[0030] In this embodiment, the lithium iron phosphate positive electrode material is prepared using the above-mentioned anhydrous iron phosphate. Since the anhydrous iron phosphate prepared in this application has the advantages of low impurity content (especially low magnesium and manganese impurity content), low sulfur content, large specific surface area, and porous structure, the lithium iron phosphate positive electrode material prepared with it as a precursor inherits the above-mentioned advantages of anhydrous iron phosphate, ensuring that industrial large-scale production can obtain pure and high-performance lithium iron phosphate positive electrode materials.
[0031] In a fourth aspect, an embodiment of the present application further provides a positive electrode plate, comprising a positive electrode collector and a positive electrode active layer disposed on at least one side of the positive electrode collector, wherein the positive electrode active layer comprises the above-mentioned lithium iron phosphate positive electrode material.
[0032] In this embodiment, the positive electrode active layer of the positive electrode plate includes the above-mentioned lithium iron phosphate positive electrode material, so the positive electrode plate including the same also has the characteristics of excellent performance.
[0033] In a fifth aspect, an embodiment of the present application further provides a secondary battery, the secondary battery comprising the above-mentioned positive electrode plate.
[0034] In this embodiment, the secondary battery includes the above-mentioned positive electrode sheet, so the secondary battery including the above-mentioned positive electrode sheet has excellent electrochemical performance.
[0035] This application has the following beneficial effects:
[0036] The present application provides a low-impurity, high-specific-surface-area ferric phosphate and a preparation method and application thereof, wherein the preparation method comprises: providing a ferrous salt solution and a mixed solution containing an oxidant and a phosphorus source; mixing the ferrous salt solution with the mixed solution, and subjecting the mixed solution to a precipitation reaction to obtain a reaction slurry; introducing an oxidizing gas into the reaction slurry, and then heating and aging the slurry to obtain a hydrated ferric phosphate slurry; and subjecting the hydrated ferric phosphate slurry to solid-liquid separation, washing, drying and sintering to obtain a low-impurity, high-specific-surface-area ferric phosphate. In the embodiments of the present application, an oxidizing gas is introduced during the crystal transformation of iron phosphate. Under the oxidizing action of the oxidizing gas, a trace amount of trivalent iron ions are always present in the system. The trivalent iron ions can suppress the formation of impurity phosphates, thereby obtaining iron phosphate with a low impurity content. At the same time, the introduced oxidizing gas also has a pore-forming effect, and can obtain iron phosphate with a porous structure and a large specific surface area. Therefore, the embodiments of the present application can prepare iron phosphate with low impurities and high specific surface area by a one-step method, which is conducive to the preparation of high-performance lithium iron phosphate positive electrode materials using the low-impurity, high specific surface area iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 This is a schematic diagram of the analysis of impurity ions entering the iron phosphate stage;
[0039] Figure 2 This is a schematic diagram of the process of anhydrous ferric phosphate prepared in this application;
[0040] Figure 3 This is a scanning electron microscope image of the anhydrous ferric phosphate prepared in Example 1 of the present application;
[0041] Figure 4 This is a scanning electron microscope image of the anhydrous ferric phosphate prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0042] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0044] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0045] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0046] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0047] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0048] At present, the synthesis method of iron phosphate can be divided into one-step synthesis and two-step synthesis according to the process route. The advantage of the one-step process is that the synthesis and aging of iron phosphate are carried out in the same equipment, and there is no need to carry out the filter pressing-rinsing-beating process of the synthetic slurry, with less equipment investment and low production cost. The disadvantage is that the impurity content of the iron phosphate product is high, mainly reflected in the Mg and Mn content of about 200ppm-300ppm. The high impurity content of iron phosphate will have an adverse effect on the specific capacity and cycle performance of the lithium iron phosphate positive electrode material; the advantage of the two-step process is that the impurity content of the prepared iron phosphate product is low, and the disadvantage is that the process flow is long, the equipment investment is large, and the production cost is slightly higher. At present, due to the problem of high impurity content in the preparation of iron phosphate by the one-step process in the industry, most manufacturers use the two-step process for the synthesis of iron phosphate.
[0049] In order to simplify the process and reduce production costs, this application chooses a one-step method for synthesis. However, the traditional one-step process has the disadvantage that the impurity content of iron phosphate is high and cannot be used as a high-performance lithium iron phosphate precursor. The inventor observed and analyzed the Mg and Mn formation stages and found that magnesium and manganese impurities quickly enter the iron phosphate during the crystal transformation of iron phosphate, and the content of trivalent iron ions in the system drops sharply at this time. Therefore, it is proposed that: in the crystal transformation stage of iron phosphate, an oxidizing gas is used for slow oxidation, so that a trace amount of trivalent iron ions continues to exist in the system to inhibit the formation of impurity phosphates, and through the pore-forming effect of the oxidizing gas, the prepared anhydrous iron phosphate has a porous structure, so that a low impurity content, a porous structure, and a large specific surface area of anhydrous iron phosphate are prepared by a one-step method.
[0050] The solution of this application is further described below.
[0051] In a first aspect, the present invention provides a method for preparing low-impurity and high specific surface area iron phosphate, which comprises:
[0052] Providing a ferrous salt solution and a mixed solution containing an oxidant and a phosphorus source;
[0053] mixing the ferrous salt solution with the mixed solution, and performing a precipitation reaction to obtain a reaction slurry;
[0054] An oxidizing gas is introduced into the reaction slurry, and then the temperature is raised and aged to obtain a hydrated iron phosphate slurry;
[0055] After solid-liquid separation, washing, drying and sintering of the hydrated iron phosphate slurry, low-impurity and high specific surface area iron phosphate is obtained.
[0056] At present, the ferrous phosphate synthesized by the traditional one-step method using ferrous sulfate, a byproduct of titanium dioxide, as the iron source generally has the problem of high impurity content in the ferrous phosphate product, especially high Mg and Mn impurity content. In order to solve the problem of high Mg and Mn impurity content in the ferrous phosphate synthesized by the traditional one-step method, the inventors analyzed and studied the formation stage of Mg and Mn impurities in the traditional one-step process (see Figure 1 ). It was found that Mg and Mn impurities quickly entered the iron phosphate crystal during the transformation of the iron phosphate crystal, and the content of trivalent iron ions in the system dropped sharply. Further analysis of iron phosphate FePO4*2H2O (Ksp=9.91*10 -16 ), magnesium phosphate Mg3(PO4)2(Ksp=1.04*10 -24 ), manganese phosphate Mn3(PO4)2 solubility product (Ksp = 6.13*10 -32 ) solubility product, it can be seen that in the same system, as long as there are trivalent iron ions in the system, it can inhibit the formation of phosphate precipitation of other impurities.
[0057] During the crystal transformation of iron phosphate, due to the rapid precipitation of trivalent iron ions in the system, the concentration of trivalent iron ions in the reaction system cannot suppress the formation of impurity phosphates in the extremely short time of the crystal transformation period. After the crystal transformation is completed, a small amount of iron phosphate is dissolved, and a small amount of trivalent iron ions exist in the system to suppress the precipitation of impurity phosphates. Therefore, it is necessary to make a large amount of trivalent iron ions exist in the reaction system, especially in the crystal transformation stage of iron phosphate, to suppress the precipitation of impurity phosphates. For this, the inventor proposes: providing a ferrous salt solution and a mixed solution containing an oxidant and a phosphorus source; mixing the ferrous salt solution with the mixed solution, and performing a precipitation reaction to obtain a reaction slurry; introducing an oxidizing gas into the reaction slurry, and then heating and aging to obtain a hydrated iron phosphate slurry; after solid-liquid separation, washing, drying and sintering of the hydrated iron phosphate slurry, a low-impurity high specific surface area iron phosphate is obtained. In the above process of crystal transformation of iron phosphate, an oxidizing gas is introduced. Under the oxidizing action of the oxidizing gas, a trace amount of trivalent iron ions are always present in the system. The trivalent iron ions can suppress the formation of impurity phosphates, thereby obtaining iron phosphate with a low impurity content. At the same time, the introduced oxidizing gas also has a pore-forming effect, and iron phosphate with a porous structure and a large specific surface area can be obtained. Therefore, the embodiment of the present application adopts a one-step method to prepare iron phosphate with low impurities and high specific surface area, which is conducive to the use of the low-impurity, high-specific surface area iron phosphate to prepare high-performance lithium iron phosphate positive electrode materials.
[0058] In an optional embodiment, the molar ratio of the oxidant in the mixed solution to the ferrous salt in the ferrous salt solution is (0.35:1)-(0.50:1);
[0059] Preferably, the oxidant includes at least one of hydrogen peroxide and ammonium persulfate.
[0060] The embodiment of the present application provides a method for preparing low-impurity and high-specific surface area ferric phosphate, wherein the molar ratio of the oxidant in the mixed solution to the ferrous salt in the ferrous salt solution is set to (0.35:1)-(0.50:1), and the above ratio is controlled so that the ferrous ions in the reaction system are not completely oxidized. In the crystal transformation stage of the ferrous phosphate, the oxidizing gas introduced can continuously oxidize the unreacted ferrous ions in the solution so that a trace amount of trivalent ferrous ions are always present in the system. The trivalent ferrous ions that continuously exist in the system can react with phosphate to form ferric phosphate, thereby inhibiting the formation of manganese phosphate and / or magnesium phosphate, thereby greatly reducing the Mg and Mn impurity content that enters the ferrous phosphate crystals in the crystal transformation stage. Optionally, the molar ratio of the oxidant in the mixed solution to the ferrous salt in the ferrous salt solution is 0.35:1, 0.36:1, 0.37:1, 0.38:1, 0.39:1, 0.40:1, 0.41:1, 0.42:1, 0.43:1, 0.44:1, 0.45:1, 0.46:1, 0.47:1, 0.48:1, 0.49:1, 0.50:1, or any value between (0.35:1)-(0.50:1).
[0061] In an optional embodiment, the aging temperature is set to 80-95° C., and after the reaction slurry changes color, the temperature is kept warm for 30-90 minutes.
[0062] The present application embodiment provides a method for preparing low-impurity high-specific surface area iron phosphate, the aging temperature is set to 80-95°C, and after the reaction slurry changes color, it is kept warm for 30-90 minutes. If the aging temperature is too high, the aging process of the iron phosphate crystals will be accelerated, resulting in thermal expansion of the crystal structure, making the crystals fragile and brittle; if the insulation time after aging is too long, the iron phosphate crystal particles may grow too large, thereby reducing the specific surface area. Optionally, the aging temperature is 80°C, 85°C, 90°C, 95°C, or any value between 80-95°C. The insulation time after aging is 30min, 40min, 50min, 60min, 70min, 80min, 90min or any value between 30-90min.
[0063] In an optional embodiment, the molar ratio of phosphorus in the mixed solution to iron in the ferrous salt solution is (1.0:1)-(1.3:1);
[0064] Preferably, the phosphorus source includes ammonium phosphate and phosphoric acid, and the ferrous salt includes ferrous sulfate;
[0065] Preferably, the ammonium phosphate salt includes at least one of diammonium phosphate and monoammonium phosphate;
[0066] Preferably, the molar ratio of ferrous salt: ammonium phosphate: phosphoric acid is 1: (0.80-1.05): (0-0.25).
[0067] The embodiment of the present application provides a method for preparing low-impurity and high-specific surface area iron phosphate. In the generation stage of amorphous iron phosphate, the molar ratio of phosphorus in the mixed solution to iron in the ferrous salt solution is controlled to be (1.0:1)-(1.3:1). If the P:Fe ratio is too low, the crystal transformation of the amorphous iron phosphate is difficult in the crystal transformation stage. If the ratio is too high, on the one hand, the phosphorus source is wasted, and on the other hand, the impurity content of the obtained iron phosphate product is too high. Optionally, the molar ratio of phosphorus in the mixed solution to iron in the ferrous salt solution is 1.0:1, 1.05:1, 1.1: 1, 1.15:1, 1.2:1, 1.25:1, 1.3:1, or any value between (1.0:1)-(1.3:1). Further, the molar ratio of ferrous salt: ammonium phosphate: phosphoric acid is controlled to be 1:(0.80-1.05):(0-0.25). Phosphoric acid is used to control the total amount of ammonium ions in the system. During the crystal transformation stage, ammonium ions can effectively prevent the agglomeration of ferric phosphate particles. The molar number of ferrous salt is 1. If the ammonium phosphate is excessive, there will be too many ammonium ions, which will make the crystal transformation of ferric phosphate difficult and generate basic ammonium ferric phosphate impurities. Optionally, the molar ratio of ferrous salt: ammonium phosphate: phosphoric acid is 1:0.80:0.20, 1:0.85:0.15, 1:0.90:0.10, 1:0.90:0.25, 1:0.95:0.15, 1:1.00:0.20 or 1:1.05:0.25, etc.
[0068] In an optional embodiment, the molar concentration of phosphate in the mixed solution is 1.0-3.0 mol / L, the molar concentration of ferrous ions in the ferrous sulfate solution is 0.5-1.5 mol / L, and the dropping time of ferrous sulfate is controlled to be 10-60 min.
[0069] The embodiment of the present application provides a method for preparing low-impurity and high specific surface area ferric phosphate. In the generation stage of amorphous ferric phosphate, the molar concentration of phosphate in the mixed solution is 1.0-3.0 mol / L, the molar concentration of ferrous ions in the ferrous sulfate solution is 0.5-1.5 mol / L, and the dripping time of ferrous sulfate is controlled to be 10-60 min. In the amorphous ferric phosphate generation stage, suitable material concentration and ferrous sulfate addition time are conducive to the reaction to generate amorphous ferric phosphate with uniform particle size. Optionally, the molar concentration of phosphate in the mixed solution is 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L or any value between 1.0-3.0 mol / L, the molar concentration of ferrous ions in the ferrous sulfate solution is 0.5 mol / L, 1.0 mol / L, or any value between 0.5-1.5 mol / L, and the ferrous sulfate addition time is 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, or any value between 10-60 min.
[0070] In some embodiments, the oxidizing gas comprises a gas containing oxygen;
[0071] Preferably, the oxidizing gas includes at least one of air, oxygen, ozone, and compressed air;
[0072] Preferably, the oxidizing gas is selected from compressed air.
[0073] The embodiments of the present application provide a method for preparing low-impurity and high-specific surface area iron phosphate. By using an oxidizing gas for slow oxidation, a trace amount of trivalent iron ions is continuously present in the system. The trivalent iron ions can inhibit the formation of impurity phosphates. In some specific embodiments, compressed air with low cost and strong oxidizing ability is preferred.
[0074] In an optional embodiment, the solid-liquid separation, washing, drying and sintering of the hydrated ferric phosphate slurry includes: filtering the hydrated ferric phosphate slurry, countercurrent washing, drying at 90-110° C., and sintering at 550-650° C. to obtain anhydrous ferric phosphate.
[0075] The embodiment of the present application provides a method for preparing low-impurity and high-specific surface area iron phosphate, wherein the hydrated iron phosphate slurry is filtered, countercurrent washed, dried at 90-110°C, and then sintered at 550-650°C to obtain anhydrous iron phosphate. The hydrated iron phosphate slurry is subjected to solid-liquid separation, washing, and then dried and sintered, which is conducive to removing the crystal water and adsorbed water contained therein, thereby obtaining a stable and high-quality anhydrous iron phosphate product. However, if the sintering temperature is too high, the iron phosphate crystal form will be converted into an α-quartz structure with poor chemical activity, so the sintering temperature must be strictly controlled. Optionally, the sintering temperature is 550°C, 570°C, 590°C, 600°C, 620°C, 640°C, 650°C, or any value between 550-650°C.
[0076] In the second aspect, the embodiment of the present application also provides a low-impurity and high specific surface area iron phosphate prepared according to the above preparation method, wherein the sulfur content of the low-impurity and high specific surface area iron phosphate is less than 100ppm, Mg is less than 60ppm, Mn is less than 60ppm, the total content of Mg+Mn is less than 100ppm, and the specific surface area is greater than 10m 2 / g.
[0077] The anhydrous iron phosphate provided in the present application is a battery-grade anhydrous iron phosphate, which has the advantages of low Mg and Mn impurity content, low sulfur content, good dispersibility, and a porous structure and large specific surface area.
[0078] In a third aspect, an embodiment of the present application further provides a lithium iron phosphate positive electrode material, the raw materials of which include the above-mentioned low-impurity and high specific surface area iron phosphate.
[0079] As can be seen from the above, the anhydrous iron phosphate prepared in the present application has the advantages of low impurity content (especially low magnesium and manganese impurity content), low sulfur content, large specific surface area and porous structure. The lithium iron phosphate positive electrode material prepared with the above-mentioned anhydrous iron phosphate as raw material is more conducive to the entry of lithium ions, and the lithiumation effect of the lithium iron phosphate positive electrode material is better; the lithium iron phosphate positive electrode material prepared with it as a precursor also has the characteristics of porous structure and large specific surface area, which increases the contact area between the electrolyte and the lithium iron phosphate positive electrode material and has good wettability, thereby giving full play to the performance of the lithium ion battery and improving the performance of the lithium ion battery; at the same time, the lithium iron phosphate positive electrode material prepared with it as a precursor also inherits the characteristics of low impurity content and low sulfur content of iron phosphate, ensuring that industrial large-scale production can obtain pure and high-performance lithium iron phosphate positive electrode materials.
[0080] In a fourth aspect, an embodiment of the present application further provides a positive electrode plate, comprising a positive electrode collector and a positive electrode active layer disposed on at least one side of the positive electrode collector, wherein the positive electrode active layer comprises the above-mentioned lithium iron phosphate positive electrode material.
[0081] The positive electrode active layer of the positive electrode plate provided in the embodiment of the present application contains the above-mentioned lithium iron phosphate positive electrode material with good performance, so the positive electrode plate containing it also has the characteristics of excellent performance.
[0082] In a fifth aspect, an embodiment of the present application further provides a secondary battery, the secondary battery comprising the above-mentioned positive electrode plate.
[0083] The secondary battery provided in the embodiment of the present application and comprising the above-mentioned positive electrode plate has excellent electrochemical performance.
[0084] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0085] 1. Preparation method
[0086] Example 1
[0087] A method for preparing low-impurity and high-specific-surface-area iron phosphate, see Figure 2 , including the following steps:
[0088] ① Preparation of ferrous salt solution: take the ferrous sulfate solution after the titanium dioxide byproduct is refined and impurities are removed, and add pure water to prepare a ferrous sulfate solution with a molar concentration of divalent iron ions of 1.0 mol / L for use;
[0089] ② Preparation of ammonium phosphate solution: add diammonium phosphate and phosphoric acid (wherein the molar ratio of ferrous sulfate: diammonium phosphate: phosphoric acid is 1:0.90:0.25, and the system P:Fe molar ratio is 1.15:1), pure water and hydrogen peroxide (wherein the molar ratio of hydrogen peroxide: ferrous sulfate is 0.35:1) to prepare an ammonium phosphate solution with a phosphate molar concentration of 2.0 mol / L for later use;
[0090] ③Synthesis of ferric phosphate: Start the reaction kettle and stir, use 100 mL of ferrous salt solution as the base liquid, and use a peristaltic pump to drop 57.5 mL of the prepared ammonium phosphate solution into the reaction kettle within 30 minutes. After the dropwise addition is completed, a reaction slurry is obtained;
[0091] ④ Crystal conversion: After the ammonium phosphate solution is added dropwise, open the compressed air pipeline, slowly blow compressed air into the reaction slurry, and heat the reaction slurry for aging. The aging temperature is set to 85°C. After the reaction slurry changes from light white to light pink, continue to keep warm for 60 minutes to obtain hydrated iron phosphate slurry;
[0092] ⑤ Preparation of anhydrous iron phosphate: Filter the hydrated iron phosphate slurry, wash, dry at 95°C, and sinter at 600°C to obtain anhydrous iron phosphate.
[0093] Example 2
[0094] ① Preparation of ferrous salt solution: take the ferrous sulfate solution after the titanium dioxide byproduct is refined and impurities are removed, and add pure water to prepare a ferrous sulfate solution with a molar concentration of divalent iron ions of 1.0 mol / L for use;
[0095] ② Preparation of ammonium phosphate solution: add diammonium phosphate and phosphoric acid (wherein the molar ratio of ferrous sulfate: diammonium phosphate: phosphoric acid is 1:0.90:0.25, and the system P:Fe molar ratio is 1.15:1), pure water and hydrogen peroxide (wherein the molar ratio of hydrogen peroxide: ferrous sulfate is 0.40:1) to prepare an ammonium phosphate solution with a phosphate molar concentration of 2.0 mol / L for use;
[0096] ③Synthesis of ferric phosphate: Start the reaction kettle and stir, use 100 mL of ferrous salt solution as the base liquid, and use a peristaltic pump to drop 57.5 mL of the prepared ammonium phosphate solution into the reaction kettle within 25 minutes. After the dropwise addition is completed, a reaction slurry is obtained;
[0097] ④ Crystal conversion: After the ammonium phosphate solution is added dropwise, open the compressed air pipeline, slowly blow compressed air into the reaction slurry, and heat the reaction slurry for aging. The aging temperature is set to 85°C. After the reaction slurry changes from light white to light pink, continue to keep warm for 60 minutes to obtain hydrated iron phosphate slurry;
[0098] ④ Preparation of anhydrous iron phosphate: Filter the hydrated iron phosphate slurry, wash it in countercurrent, dry it at 95°C, and sinter it at 600°C to obtain anhydrous iron phosphate.
[0099] Example 3
[0100] ① Preparation of ferrous salt solution: take the ferrous sulfate solution after the titanium dioxide byproduct is refined and impurities are removed, and add pure water to prepare a ferrous sulfate solution with a molar concentration of divalent iron ions of 1.0 mol / L for use;
[0101] ② Preparation of ammonium phosphate solution: add diammonium phosphate and phosphoric acid (wherein the molar ratio of ferrous sulfate: diammonium phosphate: phosphoric acid is 1:0.90:0.25, and the system P:Fe molar ratio is 1.15:1), pure water and hydrogen peroxide (wherein the molar ratio of hydrogen peroxide: ferrous sulfate is 0.50:1) to prepare an ammonium phosphate solution with a phosphate molar concentration of 2.0 mol / L for use;
[0102] ③Synthesis of ferric phosphate: Start the reaction kettle and stir, use 100 mL of ferrous salt solution as the base liquid, and use a peristaltic pump to drop 57.5 mL of the prepared ammonium phosphate solution into the reaction kettle within 40 minutes. After the dropwise addition is completed, a reaction slurry is obtained;
[0103] ④ Crystal conversion: After the ammonium phosphate solution is added dropwise, open the compressed air pipeline, slowly blow compressed air into the reaction slurry, and heat the reaction slurry for aging. The aging temperature is set to 85°C. After the reaction slurry changes from light white to light pink, continue to keep warm for 60 minutes to obtain hydrated iron phosphate slurry;
[0104] ④ Preparation of anhydrous iron phosphate: Filter the hydrated iron phosphate slurry, wash it in countercurrent, dry it at 95°C, and sinter it at 600°C to obtain anhydrous iron phosphate.
[0105] Example 4
[0106] ① Preparation of ferrous salt solution: take the ferrous sulfate solution after the titanium dioxide byproduct is refined and impurities are removed, and add pure water to prepare a ferrous sulfate solution with a molar concentration of divalent iron ions of 1.0 mol / L for use;
[0107] ② Preparation of ammonium phosphate solution: add diammonium phosphate and phosphoric acid (wherein the molar ratio of ferrous sulfate: diammonium phosphate: phosphoric acid is 1:0.80:0.20, and the system P:Fe molar ratio is 1:1), pure water and hydrogen peroxide (wherein the molar ratio of hydrogen peroxide: ferrous sulfate is 0.35:1) to prepare an ammonium phosphate solution with a phosphate molar concentration of 2.0 mol / L for use;
[0108] ③Synthesis of ferric phosphate: Start the reaction kettle and stir, use 100 mL of ferrous salt solution as the base liquid, and use a peristaltic pump to drop 50 mL of the prepared ammonium phosphate solution into the reaction kettle within 30 minutes. After the dropwise addition is completed, a reaction slurry is obtained;
[0109] ④ Crystal conversion: After the ammonium phosphate solution is added dropwise, open the compressed air pipeline, slowly blow compressed air into the reaction slurry, and heat the reaction slurry for aging. The aging temperature is set to 85°C. After the reaction slurry changes from light white to light pink, continue to keep warm for 60 minutes to obtain hydrated iron phosphate slurry;
[0110] ④ Preparation of anhydrous iron phosphate: Filter the hydrated iron phosphate slurry, wash it in countercurrent, dry it at 95°C, and sinter it at 600°C to obtain anhydrous iron phosphate.
[0111] Example 5
[0112] ① Preparation of ferrous salt solution: take the ferrous sulfate solution after the titanium dioxide byproduct is refined and impurities are removed, and add pure water to prepare a ferrous sulfate solution with a molar concentration of divalent iron ions of 1.0 mol / L for use;
[0113] ② Preparation of ammonium phosphate solution: add diammonium phosphate and phosphoric acid (wherein the molar ratio of ferrous sulfate: diammonium phosphate: phosphoric acid is 1:0.80:0.20, and the system P:Fe molar ratio is 1:1), pure water and hydrogen peroxide (wherein the molar ratio of hydrogen peroxide: ferrous sulfate is 0.40:1) to prepare an ammonium phosphate solution with a phosphate molar concentration of 2.0 mol / L for use;
[0114] ③Synthesis of ferric phosphate: Start the reaction kettle and stir, use 100 mL of ferrous salt solution as the base liquid, and use a peristaltic pump to drop 50 mL of the prepared ammonium phosphate solution into the reaction kettle within 30 minutes. After the dropwise addition is completed, a reaction slurry is obtained;
[0115] ④ Crystal conversion: After the ammonium phosphate solution is added dropwise, open the compressed air pipeline, slowly blow compressed air into the reaction slurry, and heat the reaction slurry for aging. The aging temperature is set to 85°C. After the reaction slurry changes from light white to light pink, continue to keep warm for 60 minutes to obtain hydrated iron phosphate slurry;
[0116] ④ Preparation of anhydrous iron phosphate: Filter the hydrated iron phosphate slurry, wash it in countercurrent, dry it at 95°C, and sinter it at 600°C to obtain anhydrous iron phosphate.
[0117] Example 6
[0118] ① Preparation of ferrous salt solution: take the ferrous sulfate solution after the titanium dioxide byproduct is refined and impurities are removed, and add pure water to prepare a ferrous sulfate solution with a molar concentration of divalent iron ions of 1.0 mol / L for use;
[0119] ② Preparation of ammonium phosphate solution: add diammonium phosphate and phosphoric acid (wherein the molar ratio of ferrous sulfate: diammonium phosphate: phosphoric acid is 1:0.80:0.20, and the system P:Fe molar ratio is 1:1), pure water and hydrogen peroxide (wherein the molar ratio of hydrogen peroxide: ferrous sulfate is 0.50:1) to prepare an ammonium phosphate solution with a phosphate molar concentration of 2.0 mol / L for use;
[0120] ③Synthesis of ferric phosphate: Start the reaction kettle and stir, use 100 mL of ferrous salt solution as the base liquid, and use a peristaltic pump to drop 50 mL of the prepared ammonium phosphate solution into the reaction kettle within 30 minutes. After the dropwise addition is completed, a reaction slurry is obtained;
[0121] ④ Crystal conversion: After the ammonium phosphate solution is added dropwise, open the compressed air pipeline, slowly blow compressed air into the reaction slurry, and heat the reaction slurry for aging. The aging temperature is set to 85°C. After the reaction slurry changes from light white to light pink, continue to keep warm for 60 minutes to obtain hydrated iron phosphate slurry;
[0122] ④ Preparation of anhydrous iron phosphate: Filter the hydrated iron phosphate slurry, wash it in countercurrent, dry it at 95°C, and sinter it at 600°C to obtain anhydrous iron phosphate.
[0123] Example 7
[0124] ① Preparation of ferrous salt solution: take the ferrous sulfate solution after the titanium dioxide byproduct is refined and impurities are removed, and add pure water to prepare a ferrous sulfate solution with a molar concentration of divalent iron ions of 1.0 mol / L for use;
[0125] ② Preparation of ammonium phosphate solution: add diammonium phosphate and phosphoric acid (wherein the molar ratio of ferrous sulfate: diammonium phosphate: phosphoric acid is 1:1.05:0.25, and the system P:Fe molar ratio is 1.3:1), pure water and hydrogen peroxide (wherein the molar ratio of hydrogen peroxide: ferrous sulfate is 0.35:1) to prepare an ammonium phosphate solution with a phosphate molar concentration of 2.0 mol / L for use;
[0126] ③Synthesis of ferric phosphate: Start the reactor and stir, use 100 mL of ferrous salt solution as the base liquid, and use a peristaltic pump to drop 65 mL of the prepared ammonium phosphate solution into the reactor within 30 minutes. After the dropwise addition is completed, a reaction slurry is obtained;
[0127] ④ Crystal conversion: After the ammonium phosphate solution is added dropwise, open the compressed air pipeline, slowly blow compressed air into the reaction slurry, and heat the reaction slurry for aging. The aging temperature is set to 85°C. After the reaction slurry changes from light white to light pink, continue to keep warm for 60 minutes to obtain hydrated iron phosphate slurry;
[0128] ④ Preparation of anhydrous iron phosphate: Filter the hydrated iron phosphate slurry, wash it in countercurrent, dry it at 95°C, and sinter it at 600°C to obtain anhydrous iron phosphate.
[0129] Example 8
[0130] ① Preparation of ferrous salt solution: take the ferrous sulfate solution after the titanium dioxide byproduct is refined and impurities are removed, and add pure water to prepare a ferrous sulfate solution with a molar concentration of divalent iron ions of 1.0 mol / L for use;
[0131] ② Preparation of ammonium phosphate solution: add diammonium phosphate and phosphoric acid (wherein the molar ratio of ferrous sulfate: diammonium phosphate: phosphoric acid is 1:1.05:0.25, and the system P:Fe molar ratio is 1.3:1), pure water and hydrogen peroxide (wherein the molar ratio of hydrogen peroxide: ferrous sulfate is 0.40:1) to prepare an ammonium phosphate solution with a phosphate molar concentration of 2.0 mol / L for use;
[0132] ③Synthesis of ferric phosphate: Start the reactor and stir, use 100 mL of ferrous salt solution as the base liquid, and use a peristaltic pump to drop 65 mL of the prepared ammonium phosphate solution into the reactor within 30 minutes. After the dropwise addition is completed, a reaction slurry is obtained;
[0133] ④ Crystal conversion: After the ammonium phosphate solution is added dropwise, open the compressed air pipeline, slowly blow compressed air into the reaction slurry, and heat the reaction slurry for aging. The aging temperature is set to 85°C. After the reaction slurry changes from light white to light pink, continue to keep warm for 60 minutes to obtain hydrated iron phosphate slurry;
[0134] ④ Preparation of anhydrous iron phosphate: Filter the hydrated iron phosphate slurry, wash it in countercurrent, dry it at 95°C, and sinter it at 600°C to obtain anhydrous iron phosphate.
[0135] Example 9
[0136] ① Preparation of ferrous salt solution: take the ferrous sulfate solution after the titanium dioxide byproduct is refined and impurities are removed, and add pure water to prepare a ferrous sulfate solution with a molar concentration of divalent iron ions of 1.0 mol / L for use;
[0137] ② Preparation of ammonium phosphate solution: add diammonium phosphate and phosphoric acid (wherein the molar ratio of ferrous sulfate: diammonium phosphate: phosphoric acid is 1:1.05:0.25, and the system P:Fe molar ratio is 1.3:1), pure water and hydrogen peroxide (wherein the molar ratio of hydrogen peroxide: ferrous sulfate is 0.50:1) to prepare an ammonium phosphate solution with a phosphate molar concentration of 2.0 mol / L for use;
[0138] ③Synthesis of ferric phosphate: Start the reactor and stir, use 100 mL of ferrous salt solution as the base liquid, and use a peristaltic pump to drop 65 mL of the prepared ammonium phosphate solution into the reactor within 30 minutes. After the dropwise addition is completed, a reaction slurry is obtained;
[0139] ④ Crystal conversion: After the ammonium phosphate solution is added dropwise, open the compressed air pipeline, slowly blow compressed air into the reaction slurry, and heat the reaction slurry for aging. The aging temperature is set to 85°C. After the reaction slurry changes from light white to light pink, continue to keep warm for 60 minutes to obtain hydrated iron phosphate slurry;
[0140] ④ Preparation of anhydrous iron phosphate: Filter the hydrated iron phosphate slurry, wash it in countercurrent, dry it at 95°C, and sinter it at 600°C to obtain anhydrous iron phosphate.
[0141] Comparative Example 1
[0142] A method for preparing anhydrous ferric phosphate comprises the following steps:
[0143] The ratio of hydrogen peroxide in phosphoric acid follows the conventional one-step method, with the ratio of hydrogen peroxide added being 1.2 times the total amount of completely oxidized ferrous iron to ensure complete oxidation of the ferrous iron in the system, and the compressed air slow oxidation step being eliminated. Other process conditions are the same as those in the embodiment.
[0144] ① Preparation of ferrous salt solution: take the ferrous sulfate solution after the titanium dioxide byproduct is refined and impurities are removed, and add pure water to prepare a ferrous sulfate solution with a molar concentration of divalent iron ions of 1.0 mol / L for use;
[0145] ② Preparation of ammonium phosphate solution: add diammonium phosphate and phosphoric acid (wherein the molar ratio of ferrous sulfate: diammonium phosphate: phosphoric acid is 1:0.9:0.25, and the molar ratio of P:Fe in the system is controlled at 1.15:1), pure water and hydrogen peroxide (wherein the molar ratio of hydrogen peroxide: ferrous sulfate is 0.60:1) to prepare an ammonium phosphate solution with a phosphate molar concentration of 2.0 mol / L for use;
[0146] ③ Synthesis of ferric phosphate: Start the reactor and stir, use 100 mL of ferrous salt solution as the base liquid, and use a peristaltic pump to drop 57.5 mL of the prepared ammonium phosphate solution into the reactor over 30 minutes to obtain a reaction slurry;
[0147] ④ Crystal conversion: After the ammonium phosphate solution is added dropwise, the reaction slurry is heated and aged at a temperature of 85°C. After the reaction slurry changes from light white to light pink, the temperature is kept at 60 minutes to obtain hydrated iron phosphate slurry;
[0148] ⑤ Preparation of anhydrous iron phosphate: Filter the hydrated iron phosphate slurry, wash, dry at 95°C, and sinter at 600°C to obtain anhydrous iron phosphate.
[0149] 2. Test methods and results
[0150] The following Table 1 shows the test results of the anhydrous ferric phosphate samples prepared in Examples 1-9 and Comparative Example 1. Among them, the sulfur content was detected by an infrared carbon sulfur meter, the impurity element content was detected by an inductively coupled plasma emission spectrometer (ICP), the specific surface area was detected by nitrogen adsorption method using a specific surface area tester, the iron content was detected by potassium dichromate titration method, and the phosphorus content was detected by quinoline phosphomolybdic acid weight method.
[0151] Table 1
[0152]
[0153] It can be seen from Table 1 that: Taking Example 1 as an example, the content of impurity elements such as Mg, Mn and Zn in the anhydrous iron phosphate sample prepared by the preparation method provided in Example 1 of the present application is significantly lower than the corresponding impurity element content in the anhydrous iron phosphate sample prepared by the preparation method provided in Comparative Example 1 (using the traditional one-step process), wherein the Mg content is reduced from 103.68ppm to 19.03ppm, the Mn content is reduced from 255.93ppm to 32.23ppm, and the Zn content is reduced from 45.83ppm to 9.65ppm. Similarly, the content of impurity elements such as Mg, Mn and Zn in the anhydrous iron phosphate sample prepared by the preparation method provided in Examples 2-9 of the present application is also significantly lower than the corresponding impurity element content in the anhydrous iron phosphate sample prepared by the preparation method provided in Comparative Example 1 (using the traditional one-step process). It is shown that the preparation of anhydrous iron phosphate by the preparation method provided in Examples 1-9 of the present application has a significant effect on reducing the impurity content of the traditional one-step process.
[0154] In addition, it can be seen from Table 1 that the sulfur content of the anhydrous ferric phosphate samples prepared by the preparation methods provided in Examples 1-9 of the present application is also significantly lower than that of Comparative Example 1, indicating that the preparation of anhydrous ferric phosphate by the preparation methods provided in Examples 1-9 of the present application can also reduce the sulfur content in anhydrous ferric phosphate. The scanning electron microscope image of the anhydrous ferric phosphate sample prepared by the preparation method provided in Example 1 of the present application is shown in FIG. Figure 3 ,Depend on Figure 3 It can be seen that the anhydrous iron phosphate prepared by the preparation method provided in Example 1 of the present application has a porous structure, and the impurity sulfur is more likely to escape during the sintering process of iron phosphate. Therefore, the sulfur content (33.12ppm) of the anhydrous iron phosphate sample prepared in Example 1 is lower than that of Comparative Example 1 (sulfur content 151.86ppm). Due to the reduction of the impurity content of anhydrous iron phosphate, the Fe / P ratio of the sample of Example 1 is increased from 0.9661 to 0.9748. Similarly, the Fe / P ratio of the samples of Examples 2-9 is also higher than that of Comparative Example 1, indicating that the anhydrous iron phosphate products prepared by the preparation method provided in Examples 1-9 of the present application have higher purity and better quality.
[0155] Combined with Table 1 and Figure 3-Figure 4 It can be seen that by using the compressed air slow oxidation scheme provided in Example 1 of the present application, it can be clearly observed that the anhydrous ferric phosphate primary particles are modified from the original smooth sheet structure to a porous sheet structure, and the specific surface area is increased from 8.38 m 2 / g increased to 10.71m 2 / g. This porous microstructure is more suitable for the insertion and extraction of lithium ions and for the preparation of high-performance lithium iron phosphate cathode materials.
[0156] It can be seen that the solution provided by this application can better solve the disadvantage of the traditional one-step process that it cannot be used as a high-performance lithium iron phosphate precursor due to high impurity content. At the same time, through the pore-forming effect of compressed air, a large specific surface area iron phosphate with porous flakes is obtained. The application scenarios of the one-step iron phosphate process are greatly improved, making it possible to use the iron phosphate prepared by the one-step process to prepare high-performance lithium iron phosphate positive electrode materials.
[0157] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing low-impurity and high specific surface area ferric phosphate, characterized in that: It includes: Providing a ferrous salt solution and a mixed solution containing an oxidant and a phosphorus source; Mixing the ferrous salt solution with the mixed solution to undergo precipitation reaction to obtain a reaction slurry; An oxidizing gas is introduced into the reaction slurry, and then the temperature is raised and aged to obtain a hydrated iron phosphate slurry; After solid-liquid separation, washing, drying and sintering of the hydrated ferric phosphate slurry, the low-impurity and high-specific-surface-area ferric phosphate is obtained, wherein: The molar ratio of the oxidant in the mixed solution to the ferrous salt in the ferrous salt solution is (0.35:1)-(0.50:1); The molar ratio of phosphorus in the mixed solution to iron in the ferrous salt solution is (1.0:1)-(1.3:1); The aging temperature is set at 80-95°C, and after the reaction slurry changes color, continue to keep warm for 30-90 minutes.
2. The preparation method according to claim 1, characterized in that: The oxidant comprises at least one of hydrogen peroxide and ammonium persulfate; the molar concentration of phosphate in the mixed solution is 1.0-3.0 mol / L, and the molar concentration of ferrous ions in the ferrous salt solution is 0.5-1.5 mol / L.
3. The preparation method according to claim 1, characterized in that: The phosphorus source includes ammonium phosphate and phosphoric acid, and the ferrous salt includes ferrous sulfate; the molar ratio of ferrous salt: ammonium phosphate: phosphoric acid is 1: (0.80-1.05): (0-0.25).
4. The preparation method according to claim 1, characterized in that: The oxidizing gas includes a gas containing oxygen.
5. The preparation method according to claim 4, characterized in that: The oxidizing gas includes at least one of air, oxygen, ozone and compressed air.
6. The preparation method according to claim 5, characterized in that: The oxidizing gas is selected from compressed air.
7. The preparation method according to claim 1, characterized in that: The solid-liquid separation, washing, drying and sintering of the hydrated ferric phosphate slurry comprises: filtering the hydrated ferric phosphate slurry, washing it in countercurrent, drying it at 90-110° C., and sintering it at 550-650° C. to obtain anhydrous ferric phosphate.
8. A low-impurity high specific surface area ferric phosphate prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The low-impurity and high specific surface area ferric phosphate has a sulfur content of <100ppm, Mg <60ppm, Mn <60ppm, a total content of Mg+Mn <100ppm, and a specific surface area of >10m 2 / g.
9. A lithium iron phosphate positive electrode material, characterized in that: The raw material comprises the low-impurity and high-specific-surface-area ferric phosphate as claimed in claim 8.
10. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode active layer arranged on at least one side of the positive electrode current collector, wherein the positive electrode active layer comprises the lithium iron phosphate positive electrode material according to claim 9.
11. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet according to claim 10.
Citation Information
Patent Citations
Preparation method and application of battery-grade iron phosphate precursor
CN115259124A
Preparation method of low-manganese and low-magnesium iron phosphate
CN116621141A
Cited By
A low-iron-phosphorus-ratio high-specific-surface-area iron phosphate material, a preparation method and applications thereof
CN122585974A